1995
DOI: 10.1093/ajcn/61.5.1070
|View full text |Cite
|
Sign up to set email alerts
|

The effect of raw potato starch on energy expenditure and substrate oxidation

Abstract: Because resistant starch (RS) is not absorbed as glucose in the small intestine of healthy humans, postprandial thermogenesis should be lower after the intake of RS as compared with digestible starch. To evaluate this hypothesis, we measured 5-h postprandial thermogenesis and substrate oxidation by indirect calorimetry after ingestion of 50 g pregelatinized (0% RS) and 50 g raw potato starch (54% type II RS) in 15 healthy, normal-weight young males. The subjects consumed each starch (mixed in diluted fruit syr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 25 publications
4
28
0
Order By: Relevance
“…Rats fed resistant starches consumed significantly (P<0.05) more food than rats on the control diet, yet the increased consumption did not result in increased weight gain ( Table 2). These observations are consistent with other studies where diets containing resistant starch or dietary fiber have reduced energy absorption [14][15][16]. Significant reduction of postprandial glycemia and insulinemia accompanied with reduction in subjective sensation of satiety in humans have been shown [15,17,18].…”
Section: Discussionsupporting
confidence: 91%
“…Rats fed resistant starches consumed significantly (P<0.05) more food than rats on the control diet, yet the increased consumption did not result in increased weight gain ( Table 2). These observations are consistent with other studies where diets containing resistant starch or dietary fiber have reduced energy absorption [14][15][16]. Significant reduction of postprandial glycemia and insulinemia accompanied with reduction in subjective sensation of satiety in humans have been shown [15,17,18].…”
Section: Discussionsupporting
confidence: 91%
“…Other studies examining the effect of GI on EE have been performed with simple sugars (fructose compared to glucose) (Ritz et al, 1991;Raben et al, 1994Raben et al, , 1997Tagliabue et al, 1995), where increased TEF was observed with fructose, which has a lower GI compared to glucose. Significant differences in TEF and satiety with carbohydrate foods were observed by Raben et al (1994) who noted significantly lower TEF and increased fullness with high-fibre (4.7 g/MJ) compared to low-fibre (1.7 g/MJ) meals.…”
Section: Discussionmentioning
confidence: 99%
“…They note that the cooking of savanna tubers and other plant foods would have served to both soften them and increase their energy and nutrient content. In their raw form, the starch in roots and tubers is not absorbed in the small intestine and instead is passed through the body as non-digestible carbohydrate (Tagliabue et al, 1995;Englyst and Englyst, 2005).…”
Section: Diet Qualitymentioning
confidence: 99%